THE USE OF TECHNOLOGY INTEGRATION SAMR MODEL IN TEACHING ENGLISH - Suryan Yayu Nyayu; Setiawan Heru; Sulaiman Masagus (Institut Agama Islam Negeri Palopo, 2019)
Nowadays, information and communications technology (ICT) has been widely used either in schools or colleges. An understanding on the use of technology in language learning particularly in the class fascinated for both educators and learners. One of the language learning technologies is that SAMR, a model which is designed to help educators in embedding technology skills into the learning process in the classroom. In SAMR, 4 functions used to develop the applications, as in Substitution, Augmentation, Modification and Redefenition. This model helps educators provide an overview on the implementation of English language learning (i.e. reading, writing and listening). The simple SAMR model is certainly reminiscent of a model that was first in the realm of cognitive education. This model is parallel with the model of the taxonomy of bloom, a model that is very often used in cognitive learning. By applying SAMR Model, students can design learning technology effectively.